1977
DOI: 10.1007/bf01408184
|View full text |Cite
|
Sign up to set email alerts
|

Thermal neutron capture in isotopes of nickel

Abstract: The gamma-ray spectra associated with thermal neutron capture in targets of 5SNi, 6~ 62Ni, and 64Ni have been observed with a high-sensitivity pair-spectrometer. Level schemes for the four product nuclei are discussed, correlation of widths with neutron single-particle states examined, and estimates for M1 and E2 7-ray strength functions obtained.The stable isotopes of nickel, which range in mass number from 58 to 64, fall within a mass region commanding considerable interest. In particular, since four of the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
13
0

Year Published

1979
1979
2014
2014

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 32 publications
(15 citation statements)
references
References 21 publications
2
13
0
Order By: Relevance
“…In fact, the thermal cross section obtained with the two choices is 16.2 barn for γ = 2.7 meV, but only 12.8 barn for γ = 2.4 meV. Previous measurements of the thermal cross section result in reported values between 14.0 and 21 barn [43][44][45][46][47][48][49][50], with the majority of values grouped around 14.5 barn [43,45,46,48,49]. Because of this large spread, these previous measurements cannot give us a hint on the correct γ value.…”
Section: Resonance At E R = 46 Kevmentioning
confidence: 78%
“…In fact, the thermal cross section obtained with the two choices is 16.2 barn for γ = 2.7 meV, but only 12.8 barn for γ = 2.4 meV. Previous measurements of the thermal cross section result in reported values between 14.0 and 21 barn [43][44][45][46][47][48][49][50], with the majority of values grouped around 14.5 barn [43,45,46,48,49]. Because of this large spread, these previous measurements cannot give us a hint on the correct γ value.…”
Section: Resonance At E R = 46 Kevmentioning
confidence: 78%
“…The lineshapes of the strongest v-transitions depopulating seven levels in 59Ni, two levels in 61Ni and one level in 63Ni were investigated (see Table 1). These transitions were selected because of their rather larger intensities I s which had been determined in previous (n, 7) measurements [8][9][10]. The product of capture cross-section a, isotopic abundance and relative decay intensity I s is large enough (~ 1 b).…”
Section: Experimental Set-upmentioning
confidence: 99%
“…Considering an additional systematic calibration error of 25 ppm yields a total error of 225eV. Ishaq et al [3] found B, to be 8999.91 (20) keV. This discrepancy might be explained by the fact that the calibration reference energies of lSN used by Ishaq et al seem to be systematically higher than those of the recent 14Ni(n, y) study of Kennett et al [17].…”
Section: The Sgni Level Schemementioning
confidence: 86%
“…Previous (n, ~) studies in the even-mass nickel targets [3] have shown deviations from this behaviour insofar as the primary spectra are dominated by very few strong transitions to low-lying negative-parity states which account for some 70%-90% of the primary flux. This direct mechanism thus dominates the capture process and leaves correspondingly little flux to higher excited states; this flux was not fully resolved up to now.…”
mentioning
confidence: 89%